Application of Central Composite Design Method to Oxidative Coupling Spectrophotometric Determination of Metoclopramide Hydrochloride in Pure form and Pharmaceutical Preparations - Mohanad HN Halboos (Journal of Global Pharma Technology, 2018)
A rapid, simple, and sensitive spectrophotometric method was developed for the quantitative determination of metoclopramide hydrochloride (MCP.HCl) in its pure form and in pharmaceutical formulations. The recommended method is based on the coupling between MCP.HCl (after oxidized with a NaIO4) and ellagic acid (EA) to form a colored product which shows a maximum absorption at 422 nm. In addition to univariate one factor a time optimization, chemometric central composite design (CCD) and response surface method were applied to design the experiments for three factors viz volume of oxidant, the temperature of oxidant, and temperature of coupling and to find out their optimum conditions. Under the best achieved experimental conditions, the analytical characteristics of the method were obtained. The linearity range of (MCP.HCl) is (0.1-15) μg.mL-1 at with molar absorptivity (40248.48) L.mol-1.cm-1, Sandell's sensitivity (0.00880) μg.cm-2, LOD (0.00835) μg.mL-1 and LOQ (0.02783) μg.mL-1. The results showed there are no significant interferences of additives (Exclusions) on the determination of the drug. The method proposed in this study was compared with the reference method classified in the British Pharmacopoeia and calculated F-test (0.1394) for 6 degrees of freedom and t-test (0.4517) for 12 degrees of freedom, the proposed method was found to be similar to the reference method in accuracy. The proposed method has been successfully applied for the determination of (MCP.HCl) in pure and pharmaceutical preparations (tablets, oral drops, syrups and injections).Keywords: Chemometric, Metoclopramide hydrochloride, Ellagic acid and oxidizing coupling.